2020
DOI: 10.1038/s41598-020-75890-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HMGA2 inhibitors by AlphaScreen-based ultra-high-throughput screening assays

Abstract: The mammalian high mobility group protein AT-hook 2 (HMGA2) is a multi-functional DNA-binding protein that plays important roles in tumorigenesis and adipogenesis. Previous results showed that HMGA2 is a potential therapeutic target of anticancer and anti-obesity drugs by inhibiting its DNA-binding activities. Here we report the development of a miniaturized, automated AlphaScreen ultra-high-throughput screening assay to identify inhibitors targeting HMGA2-DNA interactions. After screening the LOPAC1280 compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 67 publications
2
17
0
4
Order By: Relevance
“…Suramin is a large symmetrical molecule carrying two polysulfonated naphthyl urea groups containing six negative charges at physiological pH and therefore, the basis for its many targets is likely to be its ability to strongly bind positively charged regions in proteins such as polymerases (42,44). Indeed, we show that suramin and related compounds also inhibited the SARS-CoV-2 RdRp with micromolar IC50s without detergent sensitivity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Suramin is a large symmetrical molecule carrying two polysulfonated naphthyl urea groups containing six negative charges at physiological pH and therefore, the basis for its many targets is likely to be its ability to strongly bind positively charged regions in proteins such as polymerases (42,44). Indeed, we show that suramin and related compounds also inhibited the SARS-CoV-2 RdRp with micromolar IC50s without detergent sensitivity.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, it was excluded from further analysis. Suramin and suramin-related compounds (NF 023, PPNDS, Evans Blue and Diphenyl Blue) are heavily negatively charged molecules and may inhibit nucleic acid-binding proteins by binding to positively charged protein regions (40)(41)(42)(43)(44). They were also identified as hits in the RNAdependent RNA polymerase (RdRp) screen (Bertolin et al Biochem J, this issue) but not in other parallel screens, consistent with the ability of these polyanionic compounds to strongly inhibit certain nucleic acid-binding proteins (41,(45)(46)(47).…”
Section: Characterisation Of Hts Hitsmentioning
confidence: 99%
“…These compounds were also identified as inhibitors of SARS-CoV-2 nsp13 helicase in a parallel screen (Zeng et al [46]). Suramin and suramin-like molecules are polyanionic compounds that likely bind to positively charged patches found in a diverse array of proteins [55][56][57][58][59][60][61], including nucleic acid binding proteins like helicases [62] and viral polymerases [63][64][65][66][67]. In vitro validation experiments described in Zeng et al showed that all five compounds inhibit SARS-CoV-2 nsp13 helicase with IC 50 values between 0.5 and 6 mM and SARS-CoV-2 RdRp with IC 50 values between 0.5 and 5 mM.…”
Section: Chemical Library Screen Design and Resultsmentioning
confidence: 99%
“…Suramin seems to inhibit multiple steps in viral infection and replication: it interferes with virus-receptor interaction and hence viral–host cell binding and uptake [ 66 , 67 ], it interferes with viral helicase activities ([ 48 ] and this work) and it interferes with viral RNA polymerase activity [ 49 , 68 ]. Suramin is a large symmetrical molecule carrying two polysulfonated naphthyl urea groups containing six negative charges at physiological pH and therefore, the basis for its many targets is likely to be its ability to strongly bind positively charged regions in proteins such as polymerases [ 44 , 46 ]. Indeed, we show that suramin and related compounds also inhibited the SARS-CoV-2 RdRp with micromolar IC 50 s without detergent sensitivity.…”
Section: Discussionmentioning
confidence: 99%